The importance of security requirements in software development - Yusop, Noorrezam; Kamalrudin, Massila (Penerbit UTeM Press, 2025)
The quality of security requirements in software development is very important to increase user confidence in using software to perform online transactions such as banking, booking and online payments. Security weaknesses are a major issue that contributes to the use of insecure online technologies. When there are security weaknesses, the application is easily exposed and hacked by irresponsible hackers, which in turn allows for data and software to be compromised that can harm users. Therefore, this book provides exposure to readers on the importance of security requirements in software development. Starting with an explanation of current issues and trends in security requirements in the era of Industrial Revolution 4.0 and the transformation towards a digital economy, this book explains the attributes and threats in security requirements and the tools in security requirements. In addition, MobiMEReq, an application that helps verify user requirements for the development of mobile applications, is also introduced. This book is useful for students, researchers, and software engineering practitioners who want to know the validation of security software requirements